Pengaruh Intelectual Quotient, Emotional Quotient, dan Spiritual Quotient terhadap Minat Entrepreneur Santri di Kabupaten Banyuwangi - Yunus Zamrozi (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2019)
Effect of the intellectual quotient (IQ), emotional quotient (EQ), and spiritual quotient (SQ) persistently and simultaneously toward the entrepreneurial interest of students in Islamic boarding school (santri) in Banyuwangi Regency. This study aims to determine the effect of intellectual intelligence (IQ), emotional intelligence (EQ) and spiritual intelligence (SQ) persistently and simultaneously toward the entrepreneurial interest of students in Islamic boarding school (santri) in Banyuwangi Regency. The study used Nonprobability sampling in the form of purposive sampling. The data collection techniques used are primary data and secondary data. Primary data is obtained by means of interviews, observations and distributing questionnaires, while secondary data is obtained through documentation. Documentation techniques are used to obtain data from books, bulletin reports, and magazines considered as documentation. Interview and observation techniques were used to find out the number of students from 2016 to 2019 of Islamic Business Faculty and had attended entrepreneurship training and run entrepreneurship owned by Darussalam Islamic boarding schools and Manbaul 'Ulum Islamic boarding schools, while the questionnaires were spread to 104 respondents with the aim of finding out the answers provided by the researcher. There are 4 variables in this study, 3 independent variables namely IQ, EQ, and SQ and 1 dependent variable namely entrepreneurial interest. Data analysis in this study using multiple linear regression analysis. The results of t-test analysis (partial) of IQ, EQ, and SQ on entrepreneurial interests have a positive and significant effect, this is evidenced IQ to obtain a regression coefficient of 0.420 is positive, and the Sig. 0.0000 ≤ 0.05, EQ gets a regression coefficient of 0.407 positive, with Sig. 0.0000≤0.05, SQ gets a regression coefficient of 0.168 positive, and the Sig. 0.0004≤0.05. While the results of union analysis F (simultaneous) Intellectual intelligence, emotional intelligence and spiritual intelligence simultaneously have a positive and significant effect on interest in interest in santri entrepreneurial Islamic boarding schools in Banyuwangi Regency. This is proved by F analysis is about 195.755 ≥ F table 2.70 with the value of sig. 0,000a, based on R2 Test, intellectual intelligence, emotional intelligence and spiritual intelligence affect the interest of santri entrepreneurial boarding schools in Banyuwangi Regency by 84.4%.